Hydrothermal fluid and ore paragenesis of the gold-bearing Rattlesnake Hills Alkaline Complex, Wyoming - Ripple, Ashley, author; Ridley, John, advisor; Hannah, Judy, committee member; Sale, Tom, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: gold; alkaline; diatreme; fluid inclusions; isotopes; LA-ICP-MS